Imaging tumour heterogeneity of the consequences of a PKCα-substrate interaction in breast cancer patients - Weitsman, Gregory; Lawler, Katherine; Kelleher, Muireann T; Barrett, James E; Barber, Paul R; Shamil, Eamon; Festy, Frederic; Patel, Gargi; Fruhwirth, Gilbert O; Huang, Lufei; Tullis, Iain D C; Woodman, Natalie; et al. (Biochemical Society transactions, 2014)
Breast cancer heterogeneity demands that prognostic models must be biologically driven and recent clinical evidence indicates that future prognostic signatures need evaluation in the context of early compared with late metastatic risk prediction. In pre-clinical studies, we and others have shown that various protein-protein interactions, pertaining to the actin microfilament-associated proteins, ezrin and cofilin, mediate breast cancer cell migration, a prerequisite for cancer metastasis. Moreover, as a direct substrate for protein kinase Cα, ezrin has been shown to be a determinant of cancer metastasis for a variety of tumour types, besides breast cancer; and has been described as a pivotal regulator of metastasis by linking the plasma membrane to the actin cytoskeleton. In the present article, we demonstrate that our tissue imaging-derived parameters that pertain to or are a consequence of the PKC-ezrin interaction can be used for breast cancer prognostication, with inter-cohort reproducibility. The application of fluorescence lifetime imaging microscopy (FLIM) in formalin-fixed paraffin-embedded patient samples to probe protein proximity within the typically <10 nm range to address the oncological challenge of tumour heterogeneity, is discussed.